Concussion and executive functions in combat sports: A systematic review - Barcelos, G.; Miranda de Oliveira, J. G.; Melo, R.; Norte, C. E.; Filgueiras, A. (Journal of Sports Sciences, 2024)
Concussion is a diagnosis given due to trauma caused by abrupt acceleration and deceleration of the brain. The consequences involve, among others, impairments in executive functions. Considering the high incidence of concussions in combat sports, this study investigated the impacts of this trauma on core executive functions. A systematic search was carried out until November 2023, using the PRISMA method on the Virtual Health Library (BVS), PubMed, Science Direct and Scielo platforms. 11 studies, including case studies and quantitative empirical studies, met the eligibility criteria. Risk of bias was assessed using the Cochrane Collaboration risk of bias measurement tool. The results produced high and low bias studies, evaluated by three independent evaluators. Of the 11 studies selected, 91% included samples of boxers and 27.3% included mixed samples (men and women). The total sample was 1,130, aged between 15 and 68 years. 81.9% indicate impairment of executive functions in fighters, with impacts most frequently reported on memory (36.5%) and inhibitory control (27.5%). The results suggest that concussion impairs executive functions in boxing and MMA. However, more studies are needed to relate the diagnosis of concussion to possible deficits in executive functions in combat sports.